The Gap Between Research and Practice in the Teaching of English Pronunciation: Insights from Teachers’ Beliefs and Practices - Wahid, Ridwan; Sulong, Suhaila (IDOSI Publication, 2013)
The gap between research and practice, as in most areas of education, is prevalent in the teaching of pronunciation. This paper reviews the factors that contribute to the gap and proposes investigating teachers’ beliefs and practices as a way to address the problem. It then provides an illustration of the gap through a case study of a group of English as a Second Language (ESL) teachers at a tertiary institution. Consistent with previous studies, the teachers’ avoidance of pronunciation teaching was found to originate from their own inability to teach the skill. Closer analysis revealed that their technical knowledge in pronunciation content and pedagogy was lacking and further impoverished by their ignorance of research. However, the teachers were also found to demonstrate practical knowledge that enabled them to negotiate certain curricular and learner constraints. This latter knowledge, although efficacious, subsequently produced teaching practices that were at odds with current research. Insights from this study point to a need to close the gap not only by improving teachers’ technical knowledge but also attuning pronunciation research to serve teachers’ practical needs.